ANALISIS PERLINDUNGAN HUKUM KONSUMEN TERHADAP KLAUSULA BAKU PADA PERJANJIAN KREDIT PERBANKAN - Aprilia, Vinny; Agustini, Shenti; Situmeang, Ampuan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
The main function of the bank as a fund distributor is the basis for providing credit facilities by the bank to the community. In practice, credit is provided based on a credit agreement containing clauses that have been determined by the bank, or what is known as a standard clause. The clauses contained in the standard clause also include an exoneration clause. An exoneration clause is a clause in an agreement that refers to a part of the contract that regulates the release or transfer of special responsibilities. Although the position of the debtor in the Credit Agreement has been protected by the Consumer Protection Law, in its implementation the considerations and decisions of the judge have not fully implemented consumer protection. Therefore, the purpose of this study is to examine legal protection for debtors in standard agreements through an analysis of the considerations and decisions of the judge. The study uses a normative legal methodology, namely research that is carried out to obtain data by reviewing laws and regulations and their application in case studies. The data obtained is processed qualitatively to provide an in-depth and systematic picture of the topic discussed. The results of the study prove that consumer protection in banking credit agreements is largely determined by the judge's considerations and decisions in analyzing and interpreting the fulfillment of the valid requirements of the agreement and other laws and regulations in accordance with the positions of the parties.